1986
DOI: 10.1002/apmc.1986.051450107
|View full text |Cite
|
Sign up to set email alerts
|

Alternierende copolymere über komplexierte monomere

Abstract: Die unter präparativen Aspekten wichtigste Erkenntnis der Untersu‐chungen ist, daß die Copolymerisation ürber komplexierte Monomere iiber den gesamten Verlauf kontrolliert werden kann, und nicht– wie in der Literatur beschrieben – spontan einsetzt; von grundsltzlich‐ er Bedeutung ist der totale Ausschluß van Oxidationsmitteln (Sauer‐stoff, organische Peroxide) im System bevor die Polymerisation ge‐startet wird. Die Polyreaktion weist viele Merkmale der klassischen, nach einem Radikalkettenmechanismus ablaufend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…As has already been demonstrated, the complexation of the acceptor comonomer acrylonitrile (AN) with Lewis acids (i.e., ZnCl 2 ·Et 2 O, EtAlCl 2 ) influences the comonomer reactivities and the copolymerization parameters. ,,, Surprisingly, it was found that bipolymers with periodic comonomer sequences, ideally alternating copolymers of electron donor and acceptor comonomers, can be also synthesized in the presence of strong organic Brönsted acids. ,, This is reflected from the experimental and analytical data of a set of copolymerizations of ethene and acrylonitrile in the presence of different acids carried out at the same reaction conditions (Table , nos. 2−8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As has already been demonstrated, the complexation of the acceptor comonomer acrylonitrile (AN) with Lewis acids (i.e., ZnCl 2 ·Et 2 O, EtAlCl 2 ) influences the comonomer reactivities and the copolymerization parameters. ,,, Surprisingly, it was found that bipolymers with periodic comonomer sequences, ideally alternating copolymers of electron donor and acceptor comonomers, can be also synthesized in the presence of strong organic Brönsted acids. ,, This is reflected from the experimental and analytical data of a set of copolymerizations of ethene and acrylonitrile in the presence of different acids carried out at the same reaction conditions (Table , nos. 2−8).…”
Section: Resultsmentioning
confidence: 99%
“…It might be that the microstructure of the polymer chain with regard to the average an−et sequence length and the resulting differences in crystallite size becomes effective, which could be related to the composition of the polymerization mixture and the copolymerization conditions.
7 DSC curves of poly(ethene- alt -acrylonitrile) obtained by free radical copolymerization in the presence of ethylaluminum dichloride in CH 2 Cl 2 at −78 °C (curve 1), of almost strictly alternating ET−AN copolymer obtained by free radical copolymerization at 20 °C in TFA as solvent (mole ratio TFA/AN = 35) (curve 2), and poly(4-cyanotetramethene- stat -acrylonitrile) (curve 3, copolymer composition an/et = 1.25) obtained by free radical polymerization in CH 2 Cl 2 at 40 °C in the presence of TFA (employed mole ratio TFA/AN = 1).
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CH2 = C(Et)-end group is relatively electron-rich. We and other researchers have shown that the electrophilic character of such olefins can be enhanced by the addition of Lewis acids to the reaction mixture [8,9]. The goal of this project was to apply our knowledge and experience in the field of free radical copolymerizations of electron-rich monomers with electrophilic olefins [4,51 to the functionalization of a polyhydrocarbon with a terminal vinyl group.…”
Section: Introductionmentioning
confidence: 99%